2015
DOI: 10.1016/j.nimb.2015.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet (EUV) surface modification of polytetrafluoroethylene (PTFE) for control of biocompatibility

Abstract: a b s t r a c tExtreme ultraviolet (EUV) surface modification of polytetrafluoroethylene (PTFE) was performed in order to enhance the degree of biocompatibility. Polymer samples were irradiated by different number of EUV shots using a laser-plasma based EUV source in the presence of nitrogen gas. The physical and chemical properties of EUV modified PTFE samples were studied using Atomic Force Microscopy, X-ray photoelectron spectroscopy and water contact angle (WCA) methods. Pronounced wall type micro and nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Unlike HCV29, the cells were mostly attached to the substrate in clusters, however single dispersed cells could also be observed. Earlier studies showed that EUV processing of PTFE samples gradually oxidise the polymer surface [13]. PTFE sample irradiated with 50 EUV shots demonstrated best cancer cell adhesion and proliferation results (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Unlike HCV29, the cells were mostly attached to the substrate in clusters, however single dispersed cells could also be observed. Earlier studies showed that EUV processing of PTFE samples gradually oxidise the polymer surface [13]. PTFE sample irradiated with 50 EUV shots demonstrated best cancer cell adhesion and proliferation results (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The EUV processing resulted in formation of regular and pronounced wall type structures and modification of the surface chemical properties as described previously [13]. The HCV29 and T24 average cell number attached to polymer surface over the four day cell culture are summarized in graphical representation in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To prove the material-dependency of these processes, a standard cell culture glass and two biomaterials, polytetrafluorethylene (PTFE) and titanium, were used. These two biomaterials have a broad range of applications in regenerative medicine: PTFE polymers are used for vascular prosthesis, nerve conduits, or subcutaneous augmentation material (Ahad et al, 2015;Cheesborough et al, 2016), whereas titanium is preferably used in dental and bone replacement (Möller et al, 2012;Souza et al, 2015;Mohammed et al, 2014). In addition to the clinical relevance, the chosen materials exhibit different chemical properties, e.g., distinct water surface interaction from hydrophobic to hydrophilic material characteristics, demonstrated by decreasing water contact angles from 127.1° ±2.8° for PTFE, to 55.0° ±3.3° for titanium, down to 28.8° ±2.7° for glass.…”
Section: Isolation and Differentiation Of Human Monocytes To Macrophagesmentioning
confidence: 99%
“…However the conventional surface modification tools alter the bulk material mechanical properties [4]. Recent advancements in the laboratory scale laser produced plasma sources provide opportunities to exploit soft X-ray and extreme ultraviolet regions for applications in biomedical engineering [5][6][7][8][9]. The surface structuring of polymers by EUV photons by ablation mechanism has been demonstrated previously.…”
Section: Introductionmentioning
confidence: 98%